L’efficacité, l’égalité, l’équité et la répartition personnelle des revenus - Henry, Jacques (L'Actualité économique, 1977)
AbstractThe analysis of the impact of economic policy and of the process of growth on personal income distribution is getting greater priority in the literature. Such an analysis cannot usefully be pursued in the light of efficiency considerations alone; it must also take equality and equity into account. Equity is defined here as a characterization of a state of affairs in terms of three parameters: (1) the choice of a distributive norm, (2) the specification of what is to be distributed, and (3) a measure of the degree of inequality that exists. A general "equity function" (E) is defined, whose particular form reflects the chosen distributive norm, and whose two arguments are the sum total to be distributed and a measure of the inequality that characterizes the distribution of that sum. Then, a number of critera of distributive justice are compared, and the criteria based on the relative and absolute income gaps are found to be the most useful. This suggests the formulation of an "equity index" (e) which is sensitive to both growth, relative inequality and absolute inequality. Unsurprisingly, empirical estimates show that the "equity index" has risen in socialist countries and fallen in non-socialist countries as a group. The "equity index" is also estimated for a number of individual countries, but the results are difficult to interpret without an in depth analysis of the circumstances of each country.